„Niebo bez ptaków”. O jednym z toposów literatury lagrowej (i jego obrzeżach) - Krupiński, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The main purpose of this article is to draw attention to one of the motifs which appear regularly in literature concerning the Nazi concentration camps. In many memoirs of ex-convicts the concentration camp is represented as a place „where birds did not sing” – an area domed by an empty, silent sky, „a sky without birds”. The author of this paper examines this phenomenon from many perspectives, drawing on various types of sources. The voices of the imprisoned are surprisingly juxtaposed with ornithological research conducted by Günther Niethammer, a scientist and, simultaneously, one of the SS guards in the Auschwitz concentration camp. This article is part of ever-growing contemporary research on the topoi of concentration camp literature and Holocaust literature. Ecocriticism and environmentalism constitute an important inspiration for his text, and a post-anthropocentric perspective allows the author to extend the scope of historicity to include the non-human beings, such as animals, plants and the landscape.